2011
DOI: 10.1177/2156759x1101500203
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Culturally Relevant Stressors, Coping, Ethnic Identity, and Subjective Well-Being in Urban, Ethnic Minority Adolescents

Abstract: This study explored relations between culturally relevant stressors (i.e., urban hassles, perceived discrimination) and subjective well-being (SWB; i.e., positive/negative affect, life satisfaction) to examine whether ethnic identity and/or coping strategies would serve as moderators of the relations between stress and SWB for 157 urban, ethnic minority adolescents. Ethnic identity moderated the relation between perceived discrimination and life satisfaction. Self-distraction coping moderated the relation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…As previous research [68][69][70][71] found significant links between our sociodemographic variables (age, gender, status and school form) and the well-being and school integration of ethnic-minority youth, we included them as control variables in our study. Further, several studies [25,72] found a significant link between ethnic identification and indicators of well-being and school adjustment for adolescents; therefore, we decided to include ethnic identification as a control variable. It was measured with the item "How strongly do you feel connected to your country of origin?"…”
Section: Control Variablesmentioning
confidence: 99%
“…As previous research [68][69][70][71] found significant links between our sociodemographic variables (age, gender, status and school form) and the well-being and school integration of ethnic-minority youth, we included them as control variables in our study. Further, several studies [25,72] found a significant link between ethnic identification and indicators of well-being and school adjustment for adolescents; therefore, we decided to include ethnic identification as a control variable. It was measured with the item "How strongly do you feel connected to your country of origin?"…”
Section: Control Variablesmentioning
confidence: 99%
“…Internationally, urban communities struggle to overcome adversities such as violence (Schultz et al, 2017), weapons (Luccisano & Macdonald, 2017), poor school systems (Bruce et al, 2019), increased cost of living, poor air and water quality as well as mounting poverty (Lim et al, 2012). Adolescents growing up in low-income urban environments have been found to be exposed to a greater number of adverse childhood events (ACEs) than those in other communities (Bethell et al, 2017; Vera et al, 2011). For instance, one national survey found that 69.3% of all children and adolescents surveyed had been victimized in the previous year, and 79.6% of the 12- to 17-year-olds had been victimized before 18 years of age (Finkelhor et al, 2009).…”
Section: Stress Exposure Is High Among Youth Living In Urban Low-incmentioning
confidence: 99%
“…Others, including the current study, view trauma as having potentially cumulative effects on behavior outcomes. Chronic and cumulative trauma exposure has been conceptualized in several well-known theories, including complex trauma (Cook et al, 2017), ACEs (Wade et al, 2014) and polyvictimization (Turner et al, 2017). While these terms differ to a degree in definition and overlap to differing degrees in regard to operationalization, they also share a general common assumption that more stressors and traumas compound and contribute to negative outcomes.…”
mentioning
confidence: 99%
“…Though there is significant extant literature examining the stress experiences of Latino youth, still underdeveloped is research attending to those of recently immigrated Latino children. Stress levels among urban minority youth are important to examine due to the adverse effects of stress on academic (e.g., Crean, 2004), psychological (e.g., Vera et al, 2011), and health (e.g., White & Farrell, 2006) outcomes. In terms of educational barriers, acculturative stress may contribute to or compound achievement differences among Latino youth (Roche & Kuperminc, 2012).…”
Section: The Complex Experiences Of Latino Immigrant Youthmentioning
confidence: 99%